2022
DOI: 10.1001/jamanetworkopen.2022.48147
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Minimally Invasive vs Open Surgery for Pancreatic Adenocarcinoma

Abstract: ImportanceOnly a few high-volume centers have reported on long-term oncologic outcomes after minimally invasive pancreatic surgery (MIPS) for pancreatic adenocarcinoma, but none of them have shown superior long-term overall survival (OS) compared with open pancreatic surgery (OPS).ObjectiveTo study long-term survival after MIPS and OPS with curative intent among patients with pancreatic adenocarcinoma.Design, Setting, and ParticipantsThis comparative effectiveness study used a retrospective analysis of a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…However, more patients in the MIPS group received the more effective mFOLFIRINOX therapy (26% vs 5%). Still, survival advantages for MIPS persisted, even when statistically correcting for the type of adjuvant chemotherapy 40 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, more patients in the MIPS group received the more effective mFOLFIRINOX therapy (26% vs 5%). Still, survival advantages for MIPS persisted, even when statistically correcting for the type of adjuvant chemotherapy 40 …”
Section: Discussionmentioning
confidence: 96%
“…Still, survival advantages for MIPS persisted, even when statistically correcting for the type of adjuvant chemotherapy. 40…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic pancreaticoduodenectomy has been a major technical breakthrough worldwide, with recent systematic reviews and small randomized control trials reporting the feasibility and safety of LPD in high‐volume centres. Its proposed benefits include lower blood loss, lower morbidity, and shorter hospital stay 12–17 . The reluctance to adopt LPD in many institutions however is understandable given the surgical complexity 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Its proposed benefits include lower blood loss, lower morbidity, and shorter hospital stay. [12][13][14][15][16][17] The reluctance to adopt LPD in many institutions however is understandable given the surgical complexity. 16 In our previous study, we reported the use of HLPD as an intermediate step to achieving laparoscopic resection before attempting TLPD.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the development direction of surgery is gradually toward precision and minimally invasive, which requires us to better use endoscopic technology and surgical robot, as well as the combination of the both. Regarding some experts worried that minimally invasive treatment cannot reach the R0 margin affect the OS, disease-free survival (DFS), etc., Halit et al ( 46 ) reported a study of 396 patients with borderline resectable and resectable pancreatic adenocarcinoma, minimally invasive pancreatic surgery (MIPS) was associated with better OS and DFS than open pancreatic surgery (OPS). Centralization of MIPS should be stimulated, and pancreatic surgeons should be encouraged to pass the learning curve before implementing MIPS for pancreatic adenocarcinoma in daily clinical practice.…”
Section: Current Status Of Treatment Of Pancreatic Cancermentioning
confidence: 99%